Beyond Profit Logic: Does Organizational Mission Shape Strategic Management Accounting Effectiveness? Evidence from Islamic Educational Institutions in Indonesia - Linda Hetri Suriyanti; Mentari Dwi Aristi; Siti Afiqah Zainuddin; Fadly Ardiansyah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
Despite growing interest in Strategic Management Accounting Techniques (SMAT), their application in non-profit, values-based educational institutions remains underexplored. Muhammadiyah educational institutions (Amal Usaha Muhammadiyah/AUM) provide a unique context because they operate under Islamic organizational values while pursuing educational and social missions in an increasingly competitive educational environment. This study examines the effects of competitor accounting and strategic costing on the competitive advantage of Muhammadiyah educational institutions from the Resource-Based View (RBV) perspective. Data were collected from 107 Muhammadiyah school principals in Riau Province, representing an 84.25% response rate from a saturated sample of 127 schools. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a second-order Hierarchical Component Model (HCM). The results show that competitor accounting has a positive and significant effect on competitive advantage (β = 0.531, p < 0.001), whereas strategic costing has no significant effect (β = 0.130, p = 0.261). The model explains 32.7% of the variance in competitive advantage (R² = 0.327). These findings suggest that competitor-oriented accounting information is a more valuable strategic resource than cost-oriented techniques in values-based educational institutions. The study extends the Strategic Management Accounting and RBV literature by highlighting the importance of aligning management accounting practices with organizational mission and institutional values. Practically, Muhammadiyah school leaders should strengthen competitor intelligence and benchmarking to achieve sustainable competitive advantage.